Peran Police Goes To School dalam Meningkatkan Kesadaran Berlalu Lintas Pelajar SMA di Wilayah Hukum Polres Cianjur - Adnan Kohar (Indonesian Journal of Police Studies, 2020)
The focus of this research is motivated by the level of discipline and the level of participation of high school traffic which is relatively low, this can be proven by which traffic numbers that can be questioned by Kamseltibcarlantas in Kab. Cianjur Therefore, a study was carried out aimed at describing and analyzing the role of the Police Goes to School in increasing awareness across students and influencing factors. The concept used is the concept of the role, high school students, Dikmas Then the Police Goes To School, cross-disciplinary discipline, and uses communication theory and management theory. This study uses qualitative descriptive analysis and the data collection techniques are carried out by interview, observation and document study. Data sources include primary and secondary data. Data validity uses triangulation of sources, techniques and time. Data analysis techniques add data reduction and presentation as well as conclusions with a focus of research on the implementation of the Cianjur Regional Police Headquarters Task Force Unit. The results showed that the organization of the Police Going to School activities by the Cianjur Regional Police Traffic Unit Unit was broken down into four stages: planning, organizing, implementing and monitoring. Factors that influence the role of Police Going to School in terms of management elements namely People, Money, Methods, Materials, Machines and Markets. Meanwhile, the communication that is used is reviewed with non-active communication, namely Who, Saying It, Which Channel, For Whom, and With Effects. The conclusions obtained from the implementation of the Police Go to School activities because the role carried out with the results to be achieved has not been maximized. Factors that play a role Supporting factors and inhibiting factors. As a suggestion that is the optimal placement of members, encouraging members to be able to improve their abilities by attending vocational education, providing guidance to school security patrols (PKS), using social media and awarding (gifts) to members.